Large di- and heptafullerene poh electrolytes composed of C60 building blocks having a highly symmetrical hexakisaddition pattern - Witte, Patrick; Hörmann, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2009)
We report here on the synthesis of three new prototypes (types IIII) of very large fullerene-based polyelectrolytes which can carry up to 60 charges on their periphery. All fullerene moieties incorporated in these macromolecular structures have an octahedral hexakisaddition pattern. Dumbbell-shaped icosacarboxylate 5 (type I), which can accumulate up to twenty negative charges, is very soluble in methanol as well as in neutral and basic water. On the other hand, Janus dumbbell 13 (type II) contains both positively and negatively chargeable fullerene building blocks and is very soluble in acidic and basic media. How-ever, in the region of the isoelectric point at pH 6.0-6.5 it precipitates as a pale orange solid due to pronounced intermolecular Coulomb interactions. Giant heptafullerene 15 (type III) can store up to 60 positive charges in its periphery and is the largest molecular polyelectrolyte with defined three-dimensional structure. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.